The last party eaudiobook A novel. - Mackintosh, Clare (DC Morgan, 2022)
At midnight, one of them is dead. By morning, all of them are suspects. It's the party to end all parties . . . but not everyone is here to celebrate. On New Year's Eve, Rhys Lloyd has a house full of guests. His vacation homes on Mirror Lake are a success, and he's generously invited the village to drink champagne with their wealthy new neighbors. But by midnight, Rhys will be floating dead in the freezing waters of the lake. On New Year's Day, Ffion Morgan has a village full of suspects. The tiny community is her home, so the suspects are her neighbors, friends and family-and Ffion has her own secrets to protect. With a lie uncovered at every turn, soon the question isn't who wanted Rhys dead . . . but who finally killed him. In a village with this many secrets, murder is just the beginning.